Advanced Transact-SQL for SQL Server 2000 - Ben−Gan, Itzik (Apress, 2012)
THIS BOOK CAME ABOUT as a collaboration between two people born in different countries, during different eras in our history. Despite our dissimilar backgrounds and cultures, we have a common bondour love of Microsoft SQL Server. We have each chosen to tell you in our own words how this book came about and about the many people who helped to shape it.